Does KRAS mutation status impact the risk of local recurrence after R1 vascular resection for colorectal liver metastasis? An observational cohort study. Issue 5 (May 2020) - Procopio, Fabio; Viganò, Luca; Cimino, Matteo; Donadon, Matteo; Del Fabbro, Daniele; Torzilli, Guido
Abstract: Introduction: R0 margin is the standard in the surgical treatment of colorectal liver metastases (CLM). Recently R1 surgery, at least that enabling CLM vessel-detachment (R1vasc), seems comparable to R0. As a possible background of that biologic factors could play some role. Among them, KRAS has been investigated in the present study. Methods: Patients who underwent curative surgery for CLM between 2008 and 2016 were identified. R0, R1vasc and parenchymal R1 (R1par; tumor exposure once dissected from the parenchyma) resections with known KRAS status were analyzed. Results: Of 1000 resection areas in 340 patients, 654 (65%) R0, 98 (10%) R1vasc and 248 (25%) R1par. In mutated KRAS (mKRAS), local recurrence (LR) was similar between R0 and R1vasc (per-patient 4, 8% vs. 2%, p = 0.628; per-area 2, 1% vs. 1, 9%, p = 0.940), while higher in R1par (per-patient 25, 4% and per-area 19, 5%; p < 0.001 for both). In wild-type KRAS (wtKRAS), R0 had less LR compared to R1vasc (per-patient 7, 6% vs 14, 6%, p = 0.335; per-area 3, 1% vs 13, 3%, p = 0.012) and R1par (per-patient 18, 3%, p = 0.060; per-area 9, 9%, p = 0.013). KRAS did not impact LR in R0 (per-patient 7, 6% vs. 4, 8%, p = 0.491; per-area 3, 1% vs. 2, 1%, p = 0.555), while wtKRAS R1par had less LR compared to mKRAS R1par (per-patient 18, 3% vs 25, 4%, p = 0.404; per-area 9, 9% vs 19, 5%, p = 0.048). Inversely, LR was increased in wtKRAS R1vasc compared to mKRAS R1vasc (per-patient 14, 6% vs 2%, p = 0.043; per-area 13, 3% vs 1, 9%, p = 0.046). Conclusion: KRAS status does not impact LR risk in R0 resection. Inversely, R1vasc vs R1par LR risk is reduced in mKRAS, and increased in wtKRAS. If confirmed these results are of note.